Pemberdayaan UMKM Desa Purworejo melalui Edukasi QRIS untuk Inklusi Keuangan Digital - Mahatma Kufepaksi; Nindytia Puspitasari Dalimunthe; Sri Hasnawati; Lidya Ayuni Putri; Ahmad Faisol; Mutiasari Nur Wulan (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This activity aims to enhance the digital financial literacy of MSMEs, provide practical skills in the use of QRIS, and offer guidance in its implementation for daily transactions. Moreover, the program seeks to cultivate behavioral changes among local entrepreneurs by encouraging transparency, accountability, and technological adaptation in their business practices. Research Methodology: This activity was conducted on August 28, 2025, and was attended by 30 participants consisting of MSME owners and representatives from the Village-Owned Enterprise (BUMDes). The method used included a sharing session of QRIS and a demonstration of its practical use. Results: Participants demonstrated high levels of engagement and enthusiasm, particularly during the QRIS usage simulation. An increase in participants’ knowledge of QRIS was evident from the improvement in their pre-test (55) and post-test scores (83). Conclusions: The implementation of community service activities focused on training and mentoring in the use of QRIS for MSMEs in Purworejo Village has had a positive impact on increasing the community's digital financial literacy. Limitations: Constraints related to limited smartphone proficiency and the substantial distance to formal financial institutions resulted in this program being confined primarily to socialization efforts. It is anticipated that subsequent community engagement initiatives will be able to provide more comprehensive support, particularly in facilitating MSMEs through the formal QRIS registration and merchant onboarding process. Contributions: By equipping participants with both knowledge and hands-on experience, this initiative contributes to improve MSMEs’ knowledge of QRIS usage and encourage some business owners to begin adopting QRIS in their transactional practices.